Gender Role Beliefs and Family Migration Decision-Making - Consequences for Married Women's Economic and Labor Force Success - Thomas Cooke (European Regional Science Association (ERSA), 2005)
Despite significant gains in educational attainment and attitudes toward women in the labor force, women continue to lag behind men in economic and labor market success. The role of family migration in social science and policy discussions of this gender-gap has gone unnoticed, in spite of the fact that nearly 25 years ago the noted economist Jacob Mincer proposed that "Tied migration ranks next to child rearing as an important dampening influence in the life-cycle wage evolution of women.” Decades of family migration research have concluded that migration harms the economic and labor force status of married women, that the effect of family migration on married women cannot be entirely explained by economic factors, and that family-based gender roles likely explain much of this effect. However, only three quite limited and dated analyses have directly considered how gender-related processes contribute to the observed effects of moving on women's economic status. Thus, we are left with the conclusion that all of the empirical evidence points toward gender role beliefs as the key variable shaping family migration outcomes but without any empirical evidence to support the conclusion. This research seeks to determine if the accepted explanation for the trailing wife effect is indeed true by constructing measures of the gender role beliefs of husbands and wives and developing empirical methods for determining their effect on both the migration decision and the outcomes of migration. Data for the analysis is drawn from Waves 1 through 3 of the National Survey of Families and Households. In particular, it is expected that economically "rational” migration decisions and outcomes will only occur when both the husband and the wife share strong progressive gender role beliefs. In all other cases, the migration decision is expected to be largely dominated by the husband's labor market characteristics and that the effect of migration will be to harm the economic status of women. The analysis will provide a new and unique perspective from which to evaluate decades of evidence regarding family migration and will have an impact on public policy debates concerning the gender-gap in economic and labor market success.
Keywords: 330